(untitled) (Journal of the College of Basic Education, 2023)
1.Traditional Viewpoint:Traditional grammarians, owing to their preoccupation with the establishment of the ‘parts of speech’ and definition, have offered very little to the study of ‘ellipsis’ as a linguistic phenomenon. They have dealt with language structure on the basis of meaning. Thus, they have considered sentences as elliptical whenever there is an element which is understood but not expressed.Eckersley and Eckersley (1967:318) define ‘ellipsis’ as the part that “is missed out but is ‘understood’ by the speaker and listener”, and point out that ‘ellipsis’ is a common feature in English. Mittins (1976:52) mentions that ellipsis is the omission of items that can safely be “taken for granted”.